The Effect Of Characteristic, Psychological And Organizational Factors On Nurse Performance At Royal Prima Hospital - Abrianus Sarumaha; Ermi Girsang; Yolanda Eliza Putri Lubis; Sri Wahyuni Nasution (CV. Inara, 2023)
Nurse performance is a determining factor in the success of achieving hospital goals in nursing services. Various studies on the performance of nurses in Indonesia show that the performance of nurses is still relatively low between 47.6% - 53.4%. Nurse performance is thought to be influenced by 3 factors, namely individual factors, psychological factors and organizational factors. The purpose of this study was to analyze the effect of characteristic, psychological, and organizational factors on nurse performance. This research is a quantitative research with a cross sectional study approach. The research was conducted at the Royal Prima Hospital, Medan. The research population was 367 people, the sample obtained was 115 people. Sampling by purposive sampling. Data analysis was univariate, bivariate with chi-square test, and multivariate with multiple logistic regression at 95% confidence level ( a=0.05). The results showed that the factors that influence the performance of nurses at the Royal Prima General Hospital Medan are psychological factors (job satisfaction) (p=0.011), organizational factors (leadership and organizational culture) respectively p = 0.004 and p = 0.002. Individual characteristic factors had no effect, namely age (p=1,000), gender (p=0.661), education (p=0.454), and years of service (p=0.090). The most dominant variable influencing the nurse's performance is the leadership variable, Exp(B)/OR = 6.633, meaning that the nurse who states leadership is in a good category has a 6.6 times higher chance of having a good performance than the nurse who states that leadership is not good. It is recommended that the leadership of the Royal Prima General Hospital Medan to provide guaranteed incentives to all nurses so as to increase satisfaction. Head of the room to demonstrate leadership that is acceptable to all parties. Hospitals should maintain and improve the organizational culture that has been good so far.